Trustworthy Distributed Usage Control Enforcement in Heterogeneous Trusted Computing Environments - Wagner, Paul Georg (Karlsruher Schriften zur Anthropomatik, 2025)
Distributed usage control allows to regulate the use of data even after sharing. However, existing solutions are susceptible to manipulation by dishonest data receivers. This work investigates the use of trusted computing to achieve a trustworthy usage control enforcement process. For this, a suitable system architecture and several remote attestation protocols are designed and implemented. The resulting usage control framework is evaluated using a smart manufacturing application scenario.